Time for a Pan-Asian missile shield? - Bitzinger, Richard A. (2009)
Several Asian-Pacific states are acquiring systems to protect against ballistic missile attacks. In an environment of common threats from missile attack, it is not only increasingly possible technologically, but also increasingly logical for states in the region to cooperate in building a common missile defense shield.